The Trojan Horse Tale Revisited: An Eye on Metastatic Spread of Carcinoma Cells - Grajewski, Rafael S.; Bosch, Jacobus J.; Bruns, Heiko; Cursiefen, Claus; Heindl, Ludwig M. (Cancer Immunology Research, 2016)
The metastatic spread of carcinoma cells is not fully understood. Here, we compare the peripheral blood mononuclear cells (PBMC) and intraocular metastatic cells in parotid gland carcinoma with the PBMCs of healthy donors by immunohistochemistry and flow cytometry. We found Ber-EP4 tumor marker-positive carcinoma cells in the aqueous humor of the patient's right eye and a CD45 and Ber-EP4-expressing PBMC population in his blood. These Ber-EP4-expressing cells exhibited a monocytic-myeloid phenotype with coexpression of CD11b, CD115, and the macrophage marker CD172a (SIRP-?). Uptake of pHrodogreen revealed their phagocytic activity. Our findings suggest that the tumor cells in the anterior chamber originally derived from cell fusions between tumor cells and myeloid cells in the peripheral blood. Thus, metastases of a solid malignancy could use monocytes-macrophages as the Trojan horse to enter the eye. Cancer Immunol Res; 4(2); 92-94. ©2015 AAC
EVALuna2:25730